Impacts of a weakened AMOC on precipitation over the Euro-Atlantic region in the EC-Earth3 climate model - Bellomo K.; Meccia V. L.; D'Agostino R.; Fabiano F.; Larson S. M.; von Hardenberg J.; Corti S. (Climate Dynamics, 2023)
Given paleoclimatic evidence that the Atlantic Meridional Overturning Circulation (AMOC) may affect the global climate system, we conduct model experiments with EC-Earth3, a state-of-the-art GCM, to specifically investigate, for the first time, mechanisms of precipitation change over the Euro-Atlantic sector induced by a weakened AMOC. We artificially weaken the strength of the AMOC in the model through the release of a freshwater anomaly into the Northern Hemisphere high latitude ocean, thereby obtaining a ~ 57% weaker AMOC with respect to its preindustrial strength for 60 model years. Similar to prior studies, we find that Northern Hemisphere precipitation decreases in response to a weakened AMOC. However, we also find that the frequency of wet days increases in some regions. By computing the atmospheric moisture budget, we find that intensified but drier storms cause less precipitation over land. Nevertheless, changes in the jet stream tend to enhance precipitation over northwestern Europe. We further investigate the association of precipitation anomalies with large-scale atmospheric circulations by computing weather regimes through clustering of geopotential height daily anomalies. We find an increase in the frequency of the positive phase of the North Atlantic Oscillation (NAO+), which is associated with an increase in the occurrence of wet days over northern Europe and drier conditions over southern Europe. Since a ~ 57% reduction in the AMOC strength is within the inter-model range of projected AMOC declines by the end of the twenty-first century, our results have implications for understanding the role of AMOC in future hydrological changes.